Host genetic influences on the anthelmintic efficacy of papaya-derived cysteine proteinases in mice - Luoga, W; Mansur, F; Stepek, G; Lowe, A; Duce, IR; Buttle, DJ; Behnke, JM (Cambridge Univ Press, 2024)
Indexed by WOS/Scopus